Characteristics, diagnoses and risk profiles of inpatients readmitted within 28 days of discharge to an Australian private psychiatric hospital. (June 2020) - Keks, Nicholas A; Hope, Judith; Adamopoulos, Voula; Pring, William; Tofler, David; Macfarlane, Stephen; Van Sebille, Debbie
Objective: The objective of this study was to perform a clinical and risk audit of private hospital inpatients who had been readmitted within 28 days of a preceding admission. Method: Of 118 readmissions within 28 days in 2017 (7% of all admissions), 50 were randomly selected for audit. Characteristics, illness severity and clinical risk profiles were ascertained at discharge from the index admission and at readmission. Results: Cases were 64% female, age 49.9 ± 18.2 years (range 19–89), 40% in relationships and 24% on disability support. At readmission, 88% posed danger to self due to effects of illness, 46% had high suicide risk and 40% had high physical risk. Illness was rated as severe in 58%, while 40% were rated markedly ill. Relapse or exacerbation of major depression was a cause of readmission in 78%, relapse of alcohol/substance use requiring readmission in 22% and relapse of psychosis in 20%. Index admission length of stay of cases did not differ from that of all hospital admissions. Conclusion: Most readmitted patients were suffering severe exacerbation of depression, were acutely suicidal and were otherwise at high risk of harm. If these patients had been denied readmission on the basis of insurer funding disincentives, catastrophic outcomes may well have occurred.